(untitled) (Communications in Computational Physics, 2010)
With words as nodes, and a link exits between two neighboring words, the weighted directed English and Chinese written human language networks are constructed from one English novel and two Chinese ones. We hereby analyze in detail the topological structure of them, in order to clarify their similar and different statistical properties. The empirical results show that the English and Chinese language networks all possess the shifted power law (SPL) degree distribution, the small-world property and the hierarchical structure, the connections among the words have positive assortativity coefficient and reciprocal characteristics. We also investigate the features of the strength and the centrality, which describe the importance of a specific word. Furthermore, considering the growth properties of the language networks and part of topological property, we find that the English written human language network grows slower than the Chinese one, which implies different mechanisms of the English and Chinese languages.